Evaluation of different carbon sources used in the biofloc technology (BFT) culture of Litopenaeus vannamei. - Alaban, Leovigildo Rey S. (Miagao, Iloilo University of the Philippines Visayas, 2011)
An evaluation f different carbon sources used in Biofloc technology (BFT) culture of L. vannamei was done. The experiment included five treatments : Control, RB (Rice Bran), Tap (Tapioca, Mol (Molasses) and COMBI (Molasses + Rice Bran). Evaluation of biofloc parameters - Total Suspended Solids (TSS and Settleable Solisa (SS) - showed an increasing trend in treatments with molasses (Mol and COMBI) as the culture processed. This became significantly different (P<0.05) in the later phase of the culture. The evaluation of environmental parameters included TAN (Total Ammonia Nitrogen), NO2-N (Nitrite Nitrogen) and Chlorophyll a. In treatments with rice bran (RB and COMBI), TAN showed an increasing trend, becoming significantly different with the rest in the later phase of the culture (P < 0.05), while NO2-N were maintained below toxic levels. Chlorophyll a didn't show any discernable pattern. The effect on L. vannamei was evaluated based on growth (ABW-Average Body Weight, SGR-Specfic Growth Rate and FCR- Feed Conversion Ratio) and yield (Survival and biomass) parameters. Treatments with rice bran showed faster growth rates compared to the rest (P < 0.05) for most part of the culture period. However, analyses of growth parameters based on harvest data don't show any significant difference in SGR and final ABW for all treatments. Further, poor water quality in these treatments lead to heavy mortalities which caused FCR and Biomass to be significantly different (P < 0.05) from the rest of the treatments.
Thesis (M.S. Fisheries - Aquaculture) -- Miagao, Iloilo : U.P. Visayas, April 2011.
Keywords: carbon; Biofloc technology; Litopenaeus vannamei; Aquaculture